The protection of Human Rights and fundamental freedoms at the origins of the European integration process - Marsili, M. (Europea, 2018)
This paper aims to trace the origins of the protection of human rights and fundamental freedoms in the European integration process. It is a transcontinental journey that connects the French and the American revolution under the achievements and the principles of the Enlightenment. It is the history of contemporary Europe, from the French Revolution to the tragedy of World War II. In the process of European integration the institutions overlap, and find in the Council of Europe, an institution larger than the European Union, the moment in which these rights are codified. These principles, which are the basis of European values, have been embodied in the European Convention on Human Rights, one of the most advanced instruments on the protection of fundamental human rights.